The loss of meaning in mass McProbation and McRe-entry - Herzog-Evans, Martine (Punishment, probation and parole, 2024)
Following the ‘Sarkozy’ era (2007-2012), France has engaged in ‘zero-tolerance’ policies, which have brought an increasing number of people into the criminal justice system (CJS). In an already extremely impoverished CJS, these policies have led to serious financial problems and have made an already existing prison overcrowding problem worse. Consequently, the CJS has gradually opted for a McDonald (Ritzer, 2019; Robinson, 2019) type of offender processing, whether in prosecutor-led procedures (representing roughly half of all penal procedures: Ministry of Justice, 2019) or in the sentencing phase (Danet, 2013). A similar trend has been found in probation and in prisoner release (in French: ‘sentences’ management). The prison and probation services, which merged in 1999, have since then been in a position to benefit from the 1958 French Republic Constitution, which places the executive in a dominant position and notably allows it to draft the bills presented to a rather passive legislative power (Rousseau, 2007) and even to enjoy its own set of normative powers (‘autonomous decrees’ - Hamon & Troper, 2019). By way of law reforming (2009, 2014, and 2019 laws), the prison and probation services have thus embraced the McDonaldisation ethos. Their main obsession has been to early release as many prisoners as possible in order to free space and to accommodate more sentenced people. To do so, the prison services have created a series of so-called ‘simplified’ early release procedures, where prisoners are neither prepared for nor supported through release, where they are deprived of agency and where due process and attorney advice are removed. Behind a pretend rehabilitative discourse, the executive is only interested in efficiently flushing people out of prison; not about re-entry efficacy. As Ritzer (2019) points out, McDonaldisation often leads to counter-productive or absurd consequences. In the case of early release, the stubborn reality is that one cannot bypass actually doing the rehabilitative and re-entry work. I shall additionally argue that not everything truly qualifies as an early release measure (Ostermann, 2013). Only measures which respect prisoners’ agency prepare them for their release, which support them once they are in the community, which address their socio-psychological and criminogenic needs, and which are pronounced in the context of due process and defence rights truly qualify as such. As it is, French ‘simplified’ release procedures amount to McRe-entry and mass nothingness.